SNX9 determines the surface levels of integrin β1 in vascular endothelial cells: Implication in poor prognosis of human colorectal cancers overexpressing SNX9. Issue 10 (19th February 2019) - Tanigawa, Kazufumi; Maekawa, Masashi; Kiyoi, Takeshi; Nakayama, Jun; Kitazawa, Riko; Kitazawa, Sohei; Semba, Kentaro; Taguchi, Tomohiko; Akita, Satoshi; Yoshida, Motohira; Ishimaru, Kei; Watanabe, Yuji; et al.
Abstract: Angiogenesis, the formation of new blood vessels, is involved in a variety of diseases including the tumor growth. In response to various angiogenic stimulations, a number of proteins on the surface of vascular endothelial cells are activated to coordinate cell proliferation, migration, and spreading processes to form new blood vessels. Plasma membrane localization of these angiogenic proteins, which include vascular endothelial growth factor receptors and integrins, are warranted by intracellular membrane trafficking. Here, by using a siRNA library, we screened for the sorting nexin family that regulates intracellular trafficking and identified sorting nexin 9 (SNX9) as a novel angiogenic factor in human umbilical vein endothelial cells (HUVECs). SNX9 was essential for cell spreading on the Matrigel, and tube formation that mimics in vivo angiogenesis in HUVECs. SNX9 depletion significantly delayed the recycling of integrin β1, an essential adhesion molecule for angiogenesis, and reduced the surface levels of integrin β1 in HUVECs. Clinically, we showed that SNX9 protein was highly expressed in tumor endothelial cells of human colorectal cancer tissues. High‐level expression of SNX9 messenger RNA significantly correlated with poor prognosis of the patients with colorectal cancer. These results suggest that SNX9 is an angiogenic factor and provide a novel target for the development of new antiangiogenic drugs. Abstract : Sorting nexin 9 (SNX9) regulates recycling of integrin β1 in human vascular endothelial cells, leading to the proper angiogenesis. SNX9 is highly expressed in tumor endothelial cells and epithelial cells of human colorectal cancer tissues.